Which langauge has the Georgian Acts of the Apostles been translated from? - Bernard Outtier (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The provenance of the Georgian biblical text today too remains one of the cardinal issues of Georgian studies. Many Georgian and foreign researchers have dealt with the question of from which language the oldest Georgian recensions of the biblical books were translated. The research was conducted not in a complex way but involved separate books or recensions. In European Oriental Studies, and partly in Georgian Philological circles the idea became gradually popular which, on the basis of an analysis of concrete sources carried out by N. Marr, I. Molitor, R. Blake and others considers the Armenian trace to be a revision of the subsequent period. This idea is based on the view held in Medieval Georgia, facts of the earliest theological – philosophical terminology, the most recent philological analusis of the khanmeti fragments of biblical texts, the evidence of the historical process of Armenian-Georgian ecclesiastical and cultural relation. Bernard Outtier’s present essay deals with this issue. In particular, it gives a critique of the view on the Armenian provenance of the oldest Georgian recension of the Acts of the Apostles and concludes: “the idea of Prof. Garitte widely agreed upon in Western Europe that the Georgian Acts of the Apostles was translated from the Armenian, does not seen true”. Editor